HOW TO SOLVE RATIONAL EQUATIONS

What is a rational equation ?

A rational equation is an equation that has one or more rational expressions or more simply put, it's an equation with fractions.

And solving equations with rational expressions can be using two different methods.

Method 1 :

Step 1 :

Simplify both sides of the equation by adding/subtracting fractions to get one fraction on either side.

Step 2 :

Now, we use the Cross multiplication.

Step 3 :

Solve the transformed equation.

Method 2 :

Step 1 :

Multiply both sides of the equation by the Least common denominator to get rid of the fractions.

Step 2 :

Solve the transformed equation.

Solve and check the following rational equations.

Example 1 : Solution :

By cross multiplication, we get 12 + 3x  =  9x

12  =  9x - 3x

12  =  6x

x  =  2

Cross-check :

By applying x  =  2 in the given question, we get

4/[3(2)] + 1/3  =  1

2/3 + 1/3  =  1

1  =  1 (true)

So, the solution of x is 2.

Example 2 : Solution :

By cross multiplication, we get 5a(2)  =  5(a + 4)

10a  =  5a + 20

5a  =  20

a  =  4

Cross-check :

By applying a  =  4 in the given question, we get

[5(4)]/(4 + 4)  =  5/2

20/8  =  5/2

5/2  =  5/2 (true)

So, the solution of a is 4.

Example 3 : Solution :

By cross multiplication, we get

3(3x + 12)  =  5(x + 4)

9x + 36  =  5x + 20

9x - 5x  =  20 - 36

4x  =  -16

x  =  -4

Cross-check :

By applying x  =  -4 in the given question, we get

[3(-4) + 12]/(-4 + 4)  =  5/3

0/0  =  5/3 (false)

So, there is no solution for x.

Example 4 : Solution :

By cross multiplication, we get 18m  =  72

m  =  4

Cross-check :

By applying m  =  4 in the given question, we get

1/6 + 1/12  =  1/4

18/72  =  1/4

1/4  =  1/4 (true)

So, the solution of m is 4.

Example 5 : Solution :

By cross multiplication, we get

x(x + 6)  =  8(x + 3)

x2 + 6x  =  8x + 24

x+ 6x - 8x - 24  =  0

x2 - 2x - 24  =  0

By factorization, we get

(x - 6)(x + 4)  =  0

x - 6  =  0 and x + 4  =  0

x  =  6 and -4

Cross-check :

By applying x  =  6 in the given question, we get

6/(6 + 3)  =  8/(6 + 6)

6/9  =  8/12

2/3  =  2/3 (true)

By applying x  =  -4 in the given question, we get

-4/(-4 + 3)  =  8/(-4 + 6)

-4/(-1)  =  8/2

4/1  =  4/1 (true)

So, the solution of x is {6, -4}

Example 6 : Solution :

By cross multiplication, we get

(b - 2)(b - 5)  =  10

b2 - 5b - 2b + 10  =  10

b2 - 7b + 10 - 10  =  0

b2 - 7b  =  0

b(b - 7)  =  0

b  =  0 and b  =  7

Cross-check :

By applying b  =  0 in the given question, we get

(0 - 2)/2  =  5/(0 - 5)

(-2)/2  =  5/(-5)

-1  =  -1 (true)

By applying b  =  7 in the given question, we get

(7 - 2)/2  =  5/(7 - 5)

5/2  =  5/2 (true)

So, the solution of b is {0, 7}

Example 7 : Solution :

By cross multiplication, we get

(x + 3)(x + 3)  =  2x + 5

x2 + 3x + 3x + 9  =  2x + 5

x+ 6x + 9 - 2x - 5  =  0

x+ 4x + 4  =  0

(x + 2)(x + 2)  =  0

x  =  -2, -2

Cross-check :

By applying x  =  -2 in the given question, we get

(-2 + 3)/[2(-2) + 5]  =  1/(-2 + 3)

1/1  =  1/1 (true)

So, the solution of x is -2.

Example 8 : Solution :

By cross multiplication, we get

(y + 1)(y + 5)  =  (y + 4)(y - 1)

y2 + 5y + y + 5  =  y2 - y + 4y - 4

y+ 6y + 5  =  y+ 3y - 4

y+ 6y + 5 - y2 - 3y + 4  =  0

3y + 9  =  0

y  =  -3

Cross-check :

By applying y  =  -3 in the given question, we get

(-3 + 1)/(-3 - 1)  =  (-3 + 4)/(-3 + 5)

(-2)/(-4)  =  1/2

1/2  =  1/2 (true)

So, the solution of y is -3.

Example 9 : Solution :

By cross multiplication, we get

k2 - 2k  =  6(k - 2)

k- 2k  =  6k - 12

k- 2k - 6k + 12  =  0

k- 8k + 12  =  0

(k - 6)(k - 2)  =  0

k  =  6 and 2

Cross-check :

By applying k  =  6 in the given question, we get

1/(6 - 2)  =  6/[62 - 2(6)]

1/4  =  6/24

1/4  =  1/4 (true)

By applying k  =  2 in the given question, we get

1/(2 - 2)  =  6/[2- 2(2)]

1/0  =  6/0

=  infinity

Since it has an infinity, we can't take the k  =  2.

So, the required solution of k is 6.

Example 10 : Solution :

By cross multiplication, we get (-x + 14)(x - 2)  =  5(3x - 6)

-x2 + 2x + 14x - 28  =  15x - 30

-x2 + 16x - 28  =  15x - 30

-x2 + 16x - 28 - 15x + 30  =  0

-x+ x + 2  =  0

-(x2 - x - 2)  =  0

x- x - 2  =  0

(x - 2)(x + 1)  =  0

x  =  2 and -1

Cross-check :

By applying x  =  2 in the given question, we get

(2 + 2)/(2 - 2) - 4/3  =  5/(2 - 2)

4/0 - 4/3  =  5/0

=  infinity

Since it has an infinity, we can't take the k  =  2.

By applying x  =  -1 in the given question, we get

(-1 + 2)/(-1 - 2) - 4/3  =  5/(-1 - 2)

(-1/3) - 4/3  =  (-5/3)

-5/3  =  -5/3 (true)

So, the required solution of x is -1. Apart from the stuff given above if you need any other stuff in math, please use our google custom search here.

Kindly mail your feedback to v4formath@gmail.com

Recent Articles 1. Writing Numbers in Words Worksheet

Jan 16, 22 11:56 PM

Writing Numbers in Words Worksheet

2. Operations with Negative Numbers Worksheet

Jan 16, 22 11:40 PM

Operations with Negative Numbers Worksheet